The role of Mzansi Magic’s ‘Makoti, Are You the One’ in facilitating gender discourses - Vabaza, Ncumisa (University of the Witwatersrand, Johannesburg, 2023)
The South African Bill of rights prohibits all forms of discrimination based on gender and sex. The government through the National Development Plan encourages stakeholder involvement in the promotion of gender equality. Yet, the experiences of women in various spheres reveal that normative patriarchal socialization persists. This research evaluates the role of local media in facilitating gender discourses that permeate modern-day South African society. This research employs critical discourse analysis (CDA) and critical diversity literacy (CDL) to interpret the dominant gender discourses on the locally produced reality television show Makoti Are You the One? CDA and CDL are used to interpret the representation techniques used to empower and disempower men and women respectively. The research adopts a qualitative research approach, specifically non-participatory observation to comprehend the dynamics in the relationships between the show’s male-female participants as well as the inter-group relationships between female participants on the show. Using discourse, framing and gender theories the study provides an understanding of the techniques used by the media in representing gender, and how these contribute to the co-construction of social meanings assigned to gender. The findings show a persistent imbalance in the representation of gender through local programming, by hegemonically positioning men in superior standing to women who are represented as subjects in their homes and the broader society. These imbalances are contrary to the ideals of gender equality.
A research report submitted in partial fulfillment of the degree of Master of Arts in Critical Diversity Studies by Coursework and Research Report, to the Faculty of Humanities, School of Social Sciences, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Gender; Discourse; Representation; Media; Equality; Patriarchy; Hegemony; Reality television; UCTD; SDG-5: Gender equality